PENGUATAN MODERASI BERAGAMA DI PONDOK PESANTREN ROUDHOTUL QUR’AN 2 CIWARAK DAN KOMUNITAS NGAJI TERAS PURI KARANGGINTUNG BERBASIS ABCD UNTUK MEMBANGUN KESADARAN KEAGAMAAN INKLUSIF - Sidik Fauji; Ulul Aedi; Zein Muchamad Masykur (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
Pondok Pesantren and majlis ta'lim can become mobilizers of society in a better direction. However, both Pondok Pesantren and majlis ta'lim with strong traditions have a high potential for fanaticism. There is great potential if students or congregations have high confidence if the correct opinion is the opinion of the kyai or leader of the majlis. This service aims to strengthen the understanding of religious moderation using the Asset Based Community Development (ABCD) method. This approach leads to change, focuses on what the community wants to achieve, and helps the community realize their vision. The results of this service show that there is public understanding regarding four indicators of religious moderation, namely national commitment, tolerance, non-violence, and acceptance of tradition.